1991
DOI: 10.1002/hep.1840130219
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of interferon-producing cells in the livers of patients with chronic hepatitis B

Abstract: Cells expressing alpha- and gamma-interferon were localized in the liver tissue of patients with chronic hepatitis B by means of light and electron microscopy using monoclonal antibodies. Interferon-positive cells were regularly seen in the infiltrating mononuclear cells, and the number showed a good correlation with the degree of the necroinflammatory activity of the disease. In chronic persistent hepatitis and in normal livers, they were infrequent or virtually absent. alpha-Interferon was shown to be positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
3
9
1
Order By: Relevance
“…36,[38][39][40] Our immunohistochemical analyses showed that TLR-3 and IFN-b localize primarily to portal tract macrophages and hepatocytes, whereas IFN-a was detected primarily in inflammatory cells (plasma cells, lymphocytes, macrophages) in the portal tract and in Kupffer cells. These data are consistent with previous studies of IFN-a localization in liver biopsies from patients with viral hepatitis, [41][42][43][44][45][46] in which Kupffer cells, lymphocytes and macrophages showed IFN-a positive staining. While hepatocytes have also been previously reported to express IFNa 41,[43][44][45] in chronic viral hepatitis, the expression of IFN-b in hepatocytes has not been demonstrated by Type I interferon in primary biliary cirrhosis Y Takii et al immunohistochemistry in vivo.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…36,[38][39][40] Our immunohistochemical analyses showed that TLR-3 and IFN-b localize primarily to portal tract macrophages and hepatocytes, whereas IFN-a was detected primarily in inflammatory cells (plasma cells, lymphocytes, macrophages) in the portal tract and in Kupffer cells. These data are consistent with previous studies of IFN-a localization in liver biopsies from patients with viral hepatitis, [41][42][43][44][45][46] in which Kupffer cells, lymphocytes and macrophages showed IFN-a positive staining. While hepatocytes have also been previously reported to express IFNa 41,[43][44][45] in chronic viral hepatitis, the expression of IFN-b in hepatocytes has not been demonstrated by Type I interferon in primary biliary cirrhosis Y Takii et al immunohistochemistry in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…These data are consistent with previous studies of IFN-a localization in liver biopsies from patients with viral hepatitis, [41][42][43][44][45][46] in which Kupffer cells, lymphocytes and macrophages showed IFN-a positive staining. While hepatocytes have also been previously reported to express IFNa 41,[43][44][45] in chronic viral hepatitis, the expression of IFN-b in hepatocytes has not been demonstrated by Type I interferon in primary biliary cirrhosis Y Takii et al immunohistochemistry in vivo. Only a few report is available concerning the mRNA expression of IFN-b in hepatocytes in vivo or hepatocyte cell lines in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…Interferon (IFN) seems to be an important regulator of the local immune response in the liver of patients with chronic hepatitis B, because cells expressing IFN-a and -y are localized in the liver tissue of these patients (13 (C57BL/6 x DBA/2) mice were used to obtain fertilized eggs, and several hundred molecules of the SAP-IFN-y fragment (2.4 kb) were microinjected into the pronucleus of fertilized eggs, as described (19). When the mice were 4 weeks of age, total nucleic acid was extracted from a piece of the tail of each mouse and used for Southern blot analysis (20).…”
mentioning
confidence: 99%
“…(31). However, their expression can be induced during HBV infection (32). Our results demonstrating recognition of endogenous HBV core antigen by proliferative CD4+, class 11-restricted T cells imply that HBV-infected hepatocytes may act as APC and activate CD4 + proliferative T cells in uzvo.…”
Section: Discussionmentioning
confidence: 69%